Numerical Modelling on Load Bearing Performance of Combined Stone Column-Piled Raft Foundation in Soft Clay Soil - Danish, Ahmed (UNIMAS Institutional Repository, 2024)
An important problem encountered by foundation engineers involves soft to very soft (compressible) soils which possess low in-situ undrained shear strength (i.e., cu < 25 kPa). Foundation design in such soils is difficult at best. In many cases, deep foundations may be required to transmit foundation loads to suitable bearing strata below the soft soil deposit. Furthermore, stone columns, which consist of granular material compacted in long cylindrical holes, can be used as a technique for improving the strength and consolidation characteristics of these soils. Their costs are relatively moderate, and their installation requires medium-priced equipment. Stone columns occupy an important place and have a major role in ground treatment methods. Their use for more than 50 years in reinforcing soft soils has demonstrated their usefulness and makes them one of the most attractive methods in improving bearing capacity and reducing settlement. Unlike pile foundations, stone columns make very efficient use of the soil near the surface. These stone columns are ideal for supporting light loads, but less effective when it comes to supporting heavy loads because stone columns cannot transfer the applied stresses to the deeper layers of soil. For heavy constructions, where it is needed to transfer the applied stresses to deeper layers, piles are the most recommended foundation system. However, piles are costly, and their use is expensive. To overcome these technical and economic issues, it might be more appropriate to combine both foundations in one combined foundation system (i.e., stone column and piles used conjugally under raft foundation). In the literature, very limited work has been reported regarding the use of such a system to reinforce soft and compressible soils. Furthermore, no study was carried out to investigate the behaviour of such combined foundation system, to optimize the configuration of stone columns/piles group as combined foundation system, and to develop a theoretical model to predict the carrying capacity of the combined foundation system in soft soil capped with rigid raft foundation. Therefore, the objectives of this numerical investigation are to study the behaviour (i.e., modes of failure) of this new foundation system in order to optimize the configuration of stone columns/piles to get optimum soil improvement. For this reason, parametric study was conducted to examine the effect of the configuration and arrangement of the combined foundation system on the performance of this type of foundation system on soft soils. Also, an optimization study was conducted aiming to display the geometrical layout of stone columns/pile foundations exhibiting the superlative improvement of the performance of soil foundation. It was observed from the parametric study that combining stone columns and piles in one foundation system, improve the carrying capacity of the system, modify the soil foundation to a new upgraded composite ground, and certainly can reduce the cost of the geotechnical works. Overall, 680 combinations were investigated for this parametric study and based on the optimization study, chief leading sets were selected to get optimum soil improvement. It was noticed that these chief leading sets can increase the bearing capacity of the raft foundation by almost 50% to 90% compared to that of raft foundation resting on stone columns only. Based on the results of the optimization study, the behaviour (i.e., modes of failure) of such combined foundation system under loading was examined and it was observed that the combined foundation system fails by shear in the stone columns and soft soil, and by bearing and shear failure of pile’s tip under the rigid raft. The outcome of the observed behaviour (i.e., modes of failure) was used to develop an analytical model for predicting the carrying capacity of the combined system in soft soil.